Missing men: Differential effects of war and socialism on female labour force participation in Vietnam - Merle Kreibaum; Stephan Klasen (Georg-August-Universität Göttingen, Courant Research Centre - Poverty, Equity and Growth (CRC-PEG), 2015)
We investigate the effect of the Vietnam War and the socialist regime in the Northern part of the country on female labour force participation. We differentiate the effect across birth cohorts, thus comparing immediate and long-term impacts. After presenting a theoretical model implying effects due to the role played by the "added workers" and cultural change, we use data from three national household censuses in 1989, 1999, and 2009 to estimate probit models of determinants of women's choice to enter the labour market. Proxying war intensity with the provincial share of female population after the war, the effect of "missing men" on the work status of women is found to be positive and significant for those cohorts directly affected by the war. For those cohorts entering working age after the end of the conflict, the effect is still positive but smaller and in some specifications insignificant. Living in the Northern part of the country increases the likelihood of a woman working by around eleven percentage points, suggesting a larger and more persistent effect of socialism on female labour force participation.
Keywords: F51; J16; J20; O15; P2; 330; female labour force participation; conflict; socialism; Vietnam